Piezoelectric ceramic sensor material and preparation method thereof
By mixing rare earth elements and transition metal elements in vanadium titanic acid lead-based electrical ceramic materials, and combining SM (AL1-Ubu) O3, CUO, and LIF The shortcomings have achieved high -efficiency piezoelectric performance improvement and sintering density.
Patent Information
- Application Number
- CN202411518308.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-07
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lead zirconium titanate-based piezoelectric ceramic materials are difficult to meet the requirements of piezoelectric properties in actual production, and have a high sintering temperature and low density.
The chemical structure is (1-X) PB1-Yay (ZRZTI1-Z) O3-XSM (AL1-Ubu) O3-αWT % CUO-βWT % LIF voltage ceramic sensor material, through rare earth element A and transition metal element B The doping combines the combination of SM (AL1-Ubu) O3, CUO, and LIF to adjust the lattice distortion and sintering process of ceramics.
It improves the piezoelectric performance and density of ceramics, reduces the sintering temperature, enhances the lure temperature of the material, and is suitable for high temperature sensors.
Smart Images

Figure CN119330710A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric ceramic materials, in particular to a piezoelectric ceramic sensor material and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics are functional materials that can convert electrical quantity into mechanical quantity. In recent years, the research and application of piezoelectric ceramics have developed rapidly, and their applications can be seen everywhere in life, such as electronic sensors, lasers, medical imaging, ignition, explosions, etc.
[0003] Lead zirconate titanate-based piezoelectric ceramics are the earliest type of lead-based piezoelectric ceramics studied. Lead zirconate titanate-based piezoelectric ceramics have many advantages: high Curie temperature, high piezoelectric constant, excellent temperature stability and good time stability. At present, most studies have controlled the zirconium-titanium ratio of lead zirconate titanate-based piezoelectric ceramics and the substitution doping of A and B positions in order to obtain better piezoelectric properties, but it is far from meeting the requirements of actual production for the performance of piezoelectric ceramic materials. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a piezoelectric ceramic sensor material and a preparation method thereof.
[0005] The technical solutions adopted are as follows:
[0006] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0007] (1-x)Pb 1-y A y (Zr z Ti 1-z )O3-xSm(Al 1-u B u )O3-αwt%CuO-βwt%LiF
[0008] A is a rare earth element, and B is a transition metal element;
[0009] 0.01≤x≤0.1;
[0010] 0.01≤y≤0.1, 0.25≤z≤0.75, 0.01≤u≤0.1;
[0011] 0.1≤α≤1, 0.1≤β≤1.
[0012] Furthermore, A is La or Nd.
[0013] Furthermore, B is any one or more of Co, Ni, Mn or Zn.
[0014] Further, 0.03≤x≤0.06.
[0015] Further, x=0.05.
[0016] Further, 0.03≤y≤0.06, 0.45≤z≤0.55, 0.03≤u≤0.06.
[0017] Further, y=0.05, z=0.5, u=0.05.
[0018] Further, α=0.2, β=0.5.
[0019] The present invention also provides a method for preparing a piezoelectric ceramic sensor material:
[0020] Pb3O4, A oxide, ZrO2 and TiO2 are mixed and ball-milled, dried and pre-fired to obtain a first powder; Sm2O3, Al2O3 and B oxide are mixed and ball-milled, dried and pre-fired to obtain a second powder; the first powder, the second powder, CuO and LiF are mixed and ball-milled and dried to obtain a third powder; the third powder is granulated and sieved, pressed into billets and sintered at 1200-1300°C for 2-4 hours.
[0021] Furthermore, the pre-firing temperature of the first powder is 800-900° C., and the pre-firing time is 1-3 hours; the pre-firing temperature of the second powder is 1000-1050° C., and the pre-firing time is 1-3 hours.
[0022] Beneficial effects of the present invention:
[0023] The present invention provides a piezoelectric ceramic sensor material. Doping PZT ceramic with rare earth elements at the A position can make the ceramic have a large degree of lattice distortion, thereby improving the piezoelectric performance, and also has the effect of refining the grains and increasing the density. 1-u B u )O3 has a perovskite structure and a relatively high Curie temperature, can form a solid solution with PZT ceramics, and has a quasi-isotropic phase boundary similar to that of the traditional piezoelectric material PZT, which can accelerate the sintering densification process and improve the piezoelectric properties of the ceramic material. CuO and LiF can produce a low-melting-point liquid phase, promote particle rearrangement and dissolution precipitation, reduce the sintering temperature, and improve the sintering density. The piezoelectric ceramic sensor material prepared by the present invention not only has excellent piezoelectric properties, but also has a relatively high Curie temperature, and can be widely used in various high-temperature sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the surface SEM image of the piezoelectric ceramic sensor material prepared in Example 1. DETAILED DESCRIPTION
[0025] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0026] Embodiment 1:
[0027] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0028] 0.95Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Co 0.05 )O3-0.2wt%CuO-0.5wt%LiF
[0029] Preparation method of the above piezoelectric ceramic sensor material:
[0030] According to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2, TiO2, Sm2O3, Al2O3, Co2O3, CuO and LiF were weighed respectively. Pb3O4, La2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and Co2O3 were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was ball milled for 10 hours. h and then dried in an oven, pre-calcined at 1000°C for 3h to obtain a second powder, the first powder, the second powder, CuO and LiF are added into the ball mill of a planetary ball mill, deionized water is used as the ball milling medium, mixed and ball-milled for 5h and then dried in an oven to obtain a third powder, 8wt% polyvinyl alcohol solution is used as a binder, the third powder is granulated and passed through an 80-mesh sieve, and pressed into a green body at a pressure of 100MPa, the green body is heated to 700°C at a rate of 0.5°C / min, kept warm for 2h for debinding, and then heated to 1250°C at a rate of 5°C / min, kept warm for sintering for 2h.
[0031] Embodiment 2:
[0032] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0033] 0.95Pb 0.95 Nd 0.05 (Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Co0.05 )O3-0.2wt%CuO-0.5wt%LiF Preparation method of the above piezoelectric ceramic sensor material:
[0034] According to the proportion in the chemical structure formula, Pb3O4, Nd2O3, ZrO2, TiO2, Sm2O3, Al2O3, ZnO, Co2O3 and LiF were weighed respectively. Pb3O4, Nd2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and Co2O3 were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was ball milled for 10 hours. h and then dried in an oven, pre-calcined at 1000°C for 3h to obtain a second powder, the first powder, the second powder, CuO and LiF are added into the ball mill of a planetary ball mill, deionized water is used as the ball milling medium, mixed and ball-milled for 5h and then dried in an oven to obtain a third powder, 8wt% polyvinyl alcohol solution is used as a binder, the third powder is granulated and passed through an 80-mesh sieve, and pressed into a green body at a pressure of 100MPa, the green body is heated to 700°C at a rate of 0.5°C / min, kept warm for 2h for debinding, and then heated to 1250°C at a rate of 5°C / min, kept warm for sintering for 2h.
[0035] Embodiment 3:
[0036] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0037] 0.95Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Ni 0.05 )O3-0.2wt%CuO-0.5wt%LiF
[0038] Preparation method of the above piezoelectric ceramic sensor material:
[0039] According to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2, TiO2, Sm2O3, Al2O3, NiO, CuO and LiF were weighed respectively. Pb3O4, La2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and NiO were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. The mixture was dried in an oven and pre-calcined at 1000°C for 3h to obtain a second powder. The first powder, the second powder, CuO and LiF were added into a ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was mixed and milled for 5h and then dried in an oven to obtain a third powder. An 8wt% polyvinyl alcohol solution was used as a binder. The third powder was granulated and passed through an 80-mesh sieve. The powder was pressed into a green body at a pressure of 100MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2h, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2h.
[0040] Embodiment 4:
[0041] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0042] 0.95Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Mn 0.05 )O3-0.2wt%CuO-0.5wt%LiF Preparation method of the above piezoelectric ceramic sensor material:
[0043] According to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2, TiO2, Sm2O3, Al2O3, MnO2, CuO and LiF were weighed respectively. Pb3O4, La2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and MnO2 were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was mixed and ball milled for 10 hours. The mixture was dried in an oven and pre-calcined at 1000°C for 3 hours to obtain a second powder. The first powder, the second powder, CuO and LiF were added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixed ball milling for 5 hours, the mixture was dried in an oven to obtain a third powder. An 8wt% polyvinyl alcohol solution was used as a binder. The third powder was granulated and passed through an 80-mesh sieve. The powder was pressed into a green body at a pressure of 100 MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2 hours, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2 hours.
[0044] Embodiment 5:
[0045] A piezoelectric ceramic sensor material, the chemical structure of which is as follows:
[0046] 0.95Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Zn 0.05 )O3-0.2wt%CuO-0.5wt%LiF Preparation method of the above piezoelectric ceramic sensor material:
[0047] According to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2, TiO2, Sm2O3, Al2O3, ZnO, CuO and LiF were weighed respectively. Pb3O4, La2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and ZnO were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. The mixture was dried in an oven and pre-calcined at 1000°C for 3h to obtain a second powder. The first powder, the second powder, CuO and LiF were added into a ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was mixed and milled for 5h and then dried in an oven to obtain a third powder. An 8wt% polyvinyl alcohol solution was used as a binder. The third powder was granulated and passed through an 80-mesh sieve. The powder was pressed into a green body at a pressure of 100MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2h, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2h.
[0048] Comparative Example 1:
[0049] The same as Example 1, except that SmAlO3 is used instead of Sm(Al 0.95 Co 0.05 )O3, its chemical structure is as follows:
[0050] 0.95Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.05SmAlO3-0.2wt%CuO-0.5wt%LiF
[0051] Preparation method of the above piezoelectric ceramic sensor material:
[0052] According to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2, TiO2, Sm2O3, Al2O3, CuO and LiF were weighed respectively. Pb3O4, La2O3, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3 and Al2O3 were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. The mixture was dried and pre-calcined at 1000°C for 3h to obtain a second powder. The first powder, the second powder, CuO and LiF were added into a ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was mixed and milled for 5h and then dried in an oven to obtain a third powder. An 8wt% polyvinyl alcohol solution was used as a binder. The third powder was granulated and passed through an 80-mesh sieve. The powder was pressed into a green body at a pressure of 100MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2h, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2h.
[0053] Comparative Example 2:
[0054] It is basically the same as Example 1, except that it does not contain Sm (Al 0.95 Co 0.05 )O3, its chemical structure is as follows:
[0055] Pb 0.95 La 0.05 (Zr 0.5 Ti 0.5 )O3-0.2wt%CuO-0.5wt%LiF
[0056] Preparation method of the above piezoelectric ceramic sensor material:
[0057] Pb3O4, La2O3, ZrO2, TiO2, CuO and LiF were weighed respectively according to the proportion in the chemical structure formula, Pb3O4, La2O3, ZrO2 and TiO2 were added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain a powder. The powder, CuO and LiF were added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 5 hours, the mixture was dried in an oven, granulated with 8wt% polyvinyl alcohol solution as a binder, passed through an 80-mesh sieve, and pressed into a green body under a pressure of 100 MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2 hours, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2 hours.
[0058] Comparative Example 3:
[0059] It is basically the same as Example 1, except that La doping is not performed. Its chemical structure is as follows:
[0060] 0.95Pb(Zr 0.5 Ti 0.5 )O3-0.05Sm(Al 0.95 Co 0.05 )O3-0.2wt%CuO-0.5wt%LiF
[0061] Preparation method of the above piezoelectric ceramic sensor material:
[0062] According to the proportion in the chemical structure formula, Pb3O4, ZrO2, TiO2, Sm2O3, Al2O3, Co2O3, CuO and LiF were weighed respectively. Pb3O4, ZrO2 and TiO2 were first added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours to obtain the first powder. Sm2O3, Al2O3 and Co2O3 were then added to the ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. After mixing and ball milling for 10 hours, the mixture was dried in an oven and pre-calcined at 900°C for 2 hours. The mixture was dried and pre-calcined at 1000°C for 3h to obtain a second powder. The first powder, the second powder, CuO and LiF were added into a ball mill of a planetary ball mill, and deionized water was used as the ball milling medium. The mixture was mixed and milled for 5h and then dried in an oven to obtain a third powder. An 8wt% polyvinyl alcohol solution was used as a binder. The third powder was granulated and passed through an 80-mesh sieve. The powder was pressed into a green body at a pressure of 100MPa. The green body was heated to 700°C at a rate of 0.5°C / min, kept for debinding for 2h, and then heated to 1250°C at a rate of 5°C / min, kept for sintering for 2h.
[0063] Comparative Example 4:
[0064] It is basically the same as Example 1, except that CuO is not added.
[0065] Comparative Example 5:
[0066] It is basically the same as Example 1, except that LiF is not added.
[0067] Performance Test:
[0068] The surfaces of the piezoelectric ceramic sensor materials prepared in Examples 1-5 and Comparative Examples 1-5 were polished, coated with silver paste on both sides, kept at 750°C for 10 min, and finally polarized at a DC voltage of 4 kV / mm for 20 min in silicone oil at 120°C and placed for 24 h as samples to test their electrical properties.
[0069] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester.
[0070] The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A).
[0071] According to GBT3389.3 "Test Methods for Performance of Piezoelectric Ceramic Materials Curie Temperature T c Test》Test and calculate the Curie temperature T of the sample c ;
[0072] The test results are shown in Table 1 below:
[0073] Table 1:
[0074]
[0075] It can be seen from Table 1 above that the piezoelectric ceramic sensor material prepared in the present invention not only has excellent piezoelectric properties, but also has a relatively high Curie temperature, and can be widely used in various high-temperature sensors.
[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A piezoelectric ceramic sensor material, characterized in that: Its chemical structure is as follows: (1-x)Pb 1-y A y (Zr z Ti 1-z )O3-xSm(Al 1-u B u )O3-αwt%CuO-βwt%LiF A is a rare earth element, and B is a transition metal element; 0.01≤x≤0.1; 0.01≤y≤0.1, 0.25≤z≤0.75, 0.01≤u≤0.1; 0.1≤α≤1,0.1≤β≤1。 2. The piezoelectric ceramic sensor material according to claim 1, characterized in that: A is La or Nd.
3. The piezoelectric ceramic sensor material according to claim 1, characterized in that: B is any one or more of Co, Ni, Mn or Zn.
4. The piezoelectric ceramic sensor material according to claim 1, characterized in that: 0.03≤x≤0.06。 5. The piezoelectric ceramic sensor material according to claim 1, characterized in that: x=0.05。 6. The piezoelectric ceramic sensor material according to claim 1, characterized in that: 0.03≤y≤0.06, 0.45≤z≤0.55, 0.03≤u≤0.
06.
7. The piezoelectric ceramic sensor material according to claim 1, characterized in that: y=0.05, z=0.5, u=0.
05.
8. The piezoelectric ceramic sensor material according to claim 1, characterized in that: α=0.2,β=0.5。 9. A method for preparing a piezoelectric ceramic sensor material according to any one of claims 1 to 8, characterized in that: Pb3O4, A oxide, ZrO2 and TiO2 are mixed and ball-milled, dried and pre-fired to obtain a first powder; Sm2O3, Al2O3 and B oxide are mixed and ball-milled, dried and pre-fired to obtain a second powder; the first powder, the second powder, CuO and LiF are mixed and ball-milled and dried to obtain a third powder; the third powder is granulated and sieved, pressed into billets and sintered at 1200-1300°C for 2-4 hours.
10. The method for preparing a piezoelectric ceramic sensor material according to claim 9, characterized in that: The pre-firing temperature of the first powder is 800-900° C., and the pre-firing time is 1-3 hours. The pre-firing temperature of the second powder is 1000-1050° C., and the pre-firing time is 1-3 hours.
Citation Information
Cited By
Piezoelectric ceramic for new energy automobile and preparation method thereof
CN121405456A
Piezoelectric ceramic for new energy vehicle and preparation method thereof
CN121405456B